Pengaruh Carbon Emission Disclosure dan Green Innovation terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan yang terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Ananda, Dea; Taqwa, Salma (Jurnal Eksplorasi Akuntansi, 2024)
The purpose of this study is to analyze the effect of carbon emission disclosure, green product innovation and green process innovation on the firm value in companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. This research is quantitative research. The sampling technique uses purposive sampling. The number of samples during the research year amounted to 195 data. Hypothesis testing in this study uses multiple linear regression analysis. The results showed that carbon emission disclosure has no significant effect on firm value, green product innovation has a negative effect on firm value and green process innovation has a positive effect on firm value in companies listed on the Indonesia Stock Exchange (BEI) in the 2019-2023 period.